The Household Finance and Consumption Survey: results from the second wave (European Central Bank (ECB), 2016)
This report summarises key stylised facts from the Household Finance and Consumption Survey (HFCS) about assets and liabilities, income, and indicators of consumption and credit constraints. The second wave of the HFCS provides individual household data collected in a harmonised way in 18 euro area countries (i.e. all the euro area countries except Lithuania), as well as in Hungary and Poland.1 The total sample size is composed of more than 84,000 households. Although the survey does not refer to the same time period in all countries, the most common reference period for the data is 2014. The most common reference period for the first wave was 2010.2 The survey provides unrivalled insight into the distribution of household net wealth and its components in the euro area. However, it does not offer a complete picture of household wealth: for example, it does not include the present value of all future expected pensions, which for many households constitute a sizeable fraction of their wealth.
Keywords: D14; D31; E21; 330; assets; distribution; households; liabilities; survey; wealth